Secular changes in the anthropometrics of Chilean workers and its implication in design - Castellucci, H.I.; Viviani, C.A.; Molenbroek, J.F.M.; Arezes, P.M.; Martínez, M.; Aparici, V.; Braganza, S.; Bravo, G. (My University, 2021)
BACKGROUND:Anthropometrics is very important when ensuring a physical match between end users and product or workstations. OBJECTIVES:The purpose of this study are twofold, to provide anthropometric data for the design of products and to examine the secular changes in the adult Chilean workers in a period of more than 20 years. METHODS:Nineteen anthropometric measurements from two samples from 1995 and 2016 were compared using independent t-test (95% confidence interval), where additionally absolute and relative differences were calculated. RESULTS:The secular trend observed for Stature is characterized by an increase average of 20mm and 10.5mm per decade for females and males, respectively. There is a positive secular trend for both genders, which is observed for most of the selected body measurements. The most pronounced increases were onWeight, Shoulder breadth, Body mass index, Popliteal height; Buttock-popliteal length and Hip width. CONCLUSIONS:Segmental dimensions that experienced a positive secular trend, together with Weight and Stature, are highly correlated with seating design, addressing the need to review products targeting Chilean adult workers, such as public transport seats, office furniture or industrial workplaces.
Keywords: Design; Anthropometry; Chile; Secular trends in anthropometry